Understanding resilience in urban slums Lessons from Pedda-Jalaripeta, India - Andavarapu, Deepika; Arefi, Mahyar (AESOP, 2016)
Slums are typically perceived as substandard eyesores, corrupt, makeshift, impoverished and crime-ridden. The growing literature on resilience challenged these perceptions, and promoted new debates on their ingenuity and adaptability to overcome external circumstances. Yet these debates are often limited to short term coping and adaptive capacity of slum dwellers. In this paper we look at long-term transformation of a slum over a forty-year period. Holling’s Adaptive Cycle model is a useful tool to study the transformations occurring within a slum. The four phases of the adaptive cycle are: conservation (K), creative destruction/release (Ω), reorganization (α) and exploitation (r). The Ω and α phases are together known as the “backloop” and are the focus of this paper. This paper explores how the residents of Pedda Jalaraipeta slum in Visakhapatnam use their social capital (bonding, bridging and linkages) to survive and recover from disasters. Based on empirical ethnographic findings, this paper shows that when slum dwellers collaborate with government or non-government agencies their community can recover and retain its unique social and cultural identity.
plaNext-Next Generation Planning Vol. 2 (2016): Open Call, page 109-128
Keywords: Resilience; Adaptive Cycle; Social Capital; Bonding and Bridging; Linkage capital